Wayward Pines. [Season 1] [videorecording (DVD)] - Shyamalan, M. Night; Dillon, Matt; Howard, Terrence; Lewis, Juliette; Leo, Melissa; Gugino, Carla, 1971-; Crouch, Blake (20th Century Fox Home Entertainment, 2015)
Secret Service agent Ethan Burke wakes up in a hospital in a strangely idyllic mountain town in Idaho. But the more Ethan tries to find out what happened to him, and to two missing fellow agents, the more he discovers that nothing is as it seems in Wayward Pines. Desperate to learn the truth and return to his family, Ethan eventually unveils a terrifying secret that affects all of mankind.